Steroids: First Line Treatment in Pediatrics. Issue 2 (1995) - Spier, Sheldon
Abstract : The benefits derived from the use or inhaled steroids in pediatric asthma are reviewed in relation to the age of the patient, the delivery system and the compliance versus frequency of administration of these medications. Side effects are discussed with regard to the age or the child and the following systems: the eyes, the skin, the oropharynx, the voice, the immune system, lipid and carbohydrate metabolism, adrenal glands, bone metabolism and growth.